PUX10 Is a CDC48A Adaptor Protein That Regulates the Extraction of Ubiquitinated Oleosins from Seed Lipid Droplets in Arabidopsis. Issue 9 (7th August 2018) - Deruyffelaere, Carine; Purkrtova, Zita; Bouchez, Isabelle; Collet, Boris; Cacas, Jean-Luc; Chardot, Thierry; Gallois, Jean-Luc; D'Andrea, Sabine
Abstract : PUX10 is a CDC48A adaptor associated with lipid droplets in germinating seeds and required for the extraction of ubiquitinated oleosins from lipid droplets, a prerequisite to oleosin degradation. Abstract: Postgerminative mobilization of neutral lipids stored in seed lipid droplets (LDs) is preceded by the degradation of oleosins, the major structural LD proteins that stabilize LDs in dry seeds. We previously showed that Arabidopsis thaliana oleosins are marked for degradation by ubiquitination and are extracted from LDs before proteolysis. However, the mechanisms underlying the dislocation of these LD-anchored proteins from the LD monolayer are yet unknown. Here, we report that PUX10, a member of the plant UBX-domain containing (PUX) protein family, is an integral LD protein that associates with a subpopulation of LDs during seed germination. In pux10 mutant seedlings, PUX10 deficiency impaired the degradation of ubiquitinated oleosins and prevented the extraction of ubiquitinated oleosins from LDs. We also showed that PUX10 interacts with ubiquitin and CDC48A, the AAA ATPase Cell Division Cycle 48, through its UBA and UBX domains, respectively. Collectively, these results strongly suggest that PUX10 is an adaptor recruiting CDC48A to ubiquitinated oleosins, thus facilitating the dislocation of oleosins from LDs by the segregase activity of CDC48A. We propose that PUX10 and CDC48A are core components of a LD-associated degradation machinery, which we named the LD-associated degradation system. Importantly, PUX10 is also the first determinant of a LD subpopulation described in plants, suggesting functional differentiation of LDs in Arabidopsis seedlings.